Impact of Mature Corporate Governance on Detective Role of Forensic Accounting: Case of Public Listed Companies in Oman - Rehman, Ali; Hashim, Fathyah (KnE Social Sciences, 2019)
Organizational fraud is transpiring despite the availability of controls, regulatory directives, and governance guidelines. These controls, directives, and guidelines are only utilized as a compliance checkbox instead of being utilized to identify the control deficiencies and also to identify the maturity of corporate governance. Forensic accounting detective role is an activity which can be available within an organization that can be impacted and reformed by the mature corporate governance which can eventually assist organizations in the reduction of fraud and its related activities. Three major constituents of mature corporate governance are the board of directors, audit and risk committee, and senior management or executive management. All three significant constituents are vital to the achievement of organizational objectives and providing satisfaction to shareholders. With the utilization of agency theory, this paper intends to identify the relationship between mature corporate governance and detective role of forensic accounting within public listed companies situated in Sultanate of Oman. The descriptive cross-sectional survey has been conducted with the utilization of quantitative method, and data has been analyzed by utilization of PLS-SEM. Result suggests that mature corporate governance has a significant direct impact on forensic accounting’s detective role. In order to mitigate or eliminate fraud within organizations, it is highly recommended that organizations should have in-house forensic accounting detective role which can be strengthened with the mature corporate governance.